Meteorological conoitions in lomas of Mejia in "El Niño 1997•98" and its consequences on vegetation - Jiménez, Percy (1999)
The changes on "lomas" of Mejia -Arequipa vegetation were evaluated. In addition, temperature, solar and net global radiation, water temperature and content in the soil, and precipitation were recorded in Campbell meteorological station, located in "lomas" of Mejia, province of Islay, Department of Arequipa, Peru, at 750 msnm, among 17°03' LS and 71°50' LW; ecologically located in the Life Zone desert Brush warm Template. The average environmental temperature fluctuated between 14,1 and 19,1 °C during ENSO 1997-98 (August 97 March 98). The precipitation had two maxima, in September with 189,4 mm and 173,6 mm in February, having an accumulated of 715,4 mm. The accumulated evaporation was 271,8 mm. The evaluation on the vegetation resulted from these climatic conditions. It showed that: before "El Niño", 89 species of plants were recorded; and because an increase in abundance 01 the species and hydric soil content were obtained 170 species of plants that is an increase of 91%.